CFD simulation of dense gas dispersion in neutral atmospheric boundary layer with OpenFOAM - Tran, Vu (2022)
In this study, Monin–Obukhov similarity theory is used to specify the profiles of velocity, turbulent kinetic energy (k), and eddy dissipation rate (ϵ) in atmospheric boundary layer (ABL) flow. The OpenFOAM standard solver buoyantSimpleFoam is modified to simulate neutrally stratified ABL. The solver is able to obtain equilibrium ABL. For gas dispersion simulation, buoyantNonReactingFoam is developed to take into account fluid properties change due to temperature, buoyancy effect, and variable turbulent Schmidt number. The solver is validated for dense gas dispersion in wind tunnel test and field test of liquefied natural gas vapour dispersion in neutrally stratified ABL.